IMPLEMENTASI PENDEKATAN STEAM DI SEKOLAH DASAR: KAJIAN KONSEP, PRAKTIK, DAN TANTANGAN - Nurshabirah , Ghaidah; Risal; Dwi Fibrianti, Suzan; Alizah, Nur; Najmila, Syarifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the implementation of the Science, Technology, Engineering, Arts, and Mathematics (STEAM) approach in elementary schools through a literature study of twelve primary sources consisting of scientific journal articles and textbooks. The study aims to describe the basic concepts, implementation patterns, impact on 21st-century competencies, relevance to the Merdeka Curriculum, challenges, and best strategies in implementing STEAM in Indonesian elementary schools. The results show that STEAM is implemented primarily through three models: Project-Based Learning (PjBL), Problem-Based Learning (PBL), and Inquiry-Based Learning (IBL). Empirically, Muslimin (2025) proved the effectiveness of STEAM through a quasi-experimental design with a value of t = −5.387 (p = 0.000), where all critical thinking indicators improved from the sufficient category to very good. Nuragnia et al. (2021) noted that 93.75% of teachers had implemented PjBL/PBL, but 50% had not participated in formal STEAM training. Bancong (2024) provides a comprehensive conceptual framework encompassing integration of all STEAM elements, while Anggraeni et al. (2020) presents ten hands-on STEAM activities using simple materials. The main challenges include time constraints (78.13%), technical obstacles (75%), and lack of pedagogical support (68.75%). This study recommends continuous professional training, development of contextual STEAM modules based on local wisdom, and systematic policy support so that STEAM can be implemented effectively and sustainably within the Merdeka Curriculum framework.